Problematic of the occupation of Iraq - a study from an economic point of view. - Muzahim Al Ghurairy, Lecturer, Dr. Ali (The college of law and political science journal, 2023)
Throughout history, societies and peoples in the world go through crises thatmay be prolonged or shortened in time, depending on the comprehensiveness ofthese crises and their sources. Often these crises are of an economic nature, if notin terms of their causes, then they are also in terms of the effects they leave onhumans.There are natural disasters that cause crises such as earthquakes, hurricanes,ÁRRGVDQGGURXJKWVDQGWKHUHDUHKXPDQPDGHGLVDVWHUVVXFKDVZDUVLQYDVLRQVand occupations, and the scourge, destruction and sabotage they leave on theeconomic, social and environmental structures of the peoples to which they areexposed. An example is what happened to Iraq as a result of the Anglo-Americaninvasion and occupation in 2003, this invasion and occupation It has not happenedto any other country before it in the world at all; The economic, human, andenvironmental impacts of this occupation and its continuation were extremelytragic and catastrophic.